Single Crystal Growth and Spin Polarization Measurements of Diluted Magnetic Semiconductor (BaK)(ZnMn)2As2. Issue 1 (December 2017) - Zhao, G.; Lin, C.; Deng, Z.; Gu, G.; Yu, S.; Wang, X.; Gong, Z.; Uemera, Yasutomo J.; Li, Y.; Jin, C.
Abstract Recently a new diluted magnetic semiconductor, (Ba, K)(Zn, Mn)2 As2 (BZA), with high Curie temperature was discovered, showing an independent spin and charge-doping mechanism. This makes BZA a promising material for spintronics devices. We report the successful growth of a BZA single crystal for the first time in this study. An Andreev reflection junction, which can be used to evaluate spin polarization, was fabricated based on the BZA single crystal. A 66% spin polarization of the BZA single crystal was obtained by Andreev reflection spectroscopy analysis.